2018
DOI: 10.2147/idr.s168867
|View full text |Cite
|
Sign up to set email alerts
|

Microbial spectrum and drug-resistance profile of isolates causing bloodstream infections in febrile cancer patients at a referral hospital in Addis Ababa, Ethiopia

Abstract: BackgroundThe spectrum of pathogens causing bloodstream infections (BSIs) in cancer patients has shown significant fluctuations in different geographical areas and time. We studied the microbial spectrum and drug-resistance profile of pathogens causing BSIs in febrile cancer patients at a referral hospital in Ethiopia.MethodsThis cross-sectional study was conducted between December 2011 and June 2012 at Tikur Anbessa Hospital in Addis Ababa. Blood cultures from febrile cancer patients (n=107) were performed. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
30
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 39 publications
6
30
2
Order By: Relevance
“…All the 6 regions showed signi cantly different MRSA rates when compared to the rest of regions (all P<0.05). Ghana, an African country, saw the greatest MRSA rate (28%) which was nearly 10 times higher than the overall prevalence (49). On the contrary, four studies from different regions (Africa, Europe, Western Paci c, and Eastern Mediterranean) did not detect MRSA in BSI cases (32,34,41,50).…”
Section: Prevalence Of Mrsa-bsismentioning
confidence: 90%
See 2 more Smart Citations
“…All the 6 regions showed signi cantly different MRSA rates when compared to the rest of regions (all P<0.05). Ghana, an African country, saw the greatest MRSA rate (28%) which was nearly 10 times higher than the overall prevalence (49). On the contrary, four studies from different regions (Africa, Europe, Western Paci c, and Eastern Mediterranean) did not detect MRSA in BSI cases (32,34,41,50).…”
Section: Prevalence Of Mrsa-bsismentioning
confidence: 90%
“…Among a subset of 23 studies that contained data on 3690 Gram-positive BSI cases, the MRSA isolation rate in Gram-positive bacteria was 10% (95% CI 6-14%) (5,13,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(48)(49)(50). In 15 studies whose number of S. aureus was more than 10, the pooled prevalence of MRSA among S. aureus was 44% (95% CI 32-57%) (5,13,29,33,35,37,39,(42)(43)(44)(45)(46)(47)(48)(49).…”
Section: Prevalence Of Mrsa-bsismentioning
confidence: 99%
See 1 more Smart Citation
“…Among a subset of 23 studies that contained data on 3690 Gram-positive BSI cases, the MRSA isolation rate in Gram-positive bacteria was 10% (95% CI 6-14%) (5,13,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(47)(48)(49). In 15 studies whose number of S. aureus was more than 10, the pooled prevalence of MRSA among S. aureus was 44% (95% CI 32-57%) (5,13,28,32,34,36,38,(41)(42)(43)(44)(45)(46)(47)(48).…”
Section: Prevalence Of Mrsa-bsismentioning
confidence: 99%
“…Based on data from 16 studies on 8461 adult BSI isolates, the MRSA isolation rate among BSIs in adults was 4% (95% CI 3-6%) (5,13,28,31,32,35,36,38,39,41,(43)(44)(45)(46)(47)(48). Besides, ve studies reported data on 927 BSI isolates from children and the MRSA prevalence in this population was 2% (95% CI 0-5%) (30,33,37,42,49).…”
Section: Prevalence Of Mrsa-bsismentioning
confidence: 99%